Methods to Quantify In-Field Nutrient Leaching - Bibek Acharya; Vivek Sharma; Charles Barrett; Sudeep Singh Sidhu; Lincoln Zotarelli; Michael D. Dukes (EDIS)
This publication summarizes the basic concepts of three most-used NO3-N leaching quantification methods in field conditions. Written by Bibek Acharya, Vivek Sharma, Charles Barrett, Sudeep Singh Sidhu, Lincoln Zotarelli, and Michael D. Dukes, and published by the UF/IFAS Department of Agricultural and Biological Engineering, December 2022.